A dynamic rRNA ribomethylome drives stemness in acute myeloid leukemia - Zhou, Fengbiao; Aroua, Nesrine; Liu, Yi; Rohde, Christian; Cheng, Jingdong; Wirth, Anna-Katharina; Fijalkowska, Daria; Göllner, Stefanie; Lotze, Michelle; Yun, Haiyang; Yu, Xiaobing; Pabst, Caroline; et al. (Cancer discovery, 2023)
The development and regulation of malignant self-renewal remain unresolved issues. Here, we provide biochemical, genetic, and functional evidence that dynamics in ribosomal RNA (rRNA) 2′-O-methylation regulate leukemia stem cell (LSC) activity in vivo. A comprehensive analysis of the rRNA 2′-O-methylation landscape of 94 patients with acute myeloid leukemia (AML) revealed dynamic 2′-O-methylation specifically at exterior sites of ribosomes. The rRNA 2′-O-methylation pattern is closely associated with AML development stage and LSC gene expression signature. Forced expression of the 2′-O-methyltransferase fibrillarin (FBL) induced an AML stem cell phenotype and enabled engraftment of non-LSC leukemia cells in NSG mice. Enhanced 2′-O-methylation redirected the ribosome translation program toward amino acid transporter mRNAs enriched in optimal codons and subsequently increased intracellular amino acid levels. Methylation at the single site 18S-guanosine 1447 was instrumental for LSC activity. Collectively, our work demonstrates that dynamic 2′-O-methylation at specific sites on rRNAs shifts translational preferences and controls AML LSC self-renewal.We establish the complete rRNA 2′-O-methylation landscape in human AML. Plasticity of rRNA 2′-O-methylation shifts protein translation toward an LSC phenotype. This dynamic process constitutes a novel concept of how cancers reprogram cell fate and function.This article is highlighted in the In This Issue feature, p. 247